Improving Student Learning Outcomes with the Application of Problem Based Learning Models in Microprocessor and Microcontroller Subjects at SMK Negeri 2 Pematangsiantar - Samosir, Beslon (Future Science / FSH-PH Publications, 2022)
The objectives of this Classroom Action Research were to determine: (1) increase student activity during the learning process of Microprocessors and Microcontrollers by applying the Problem Based Learning model at SMK Negeri 2 Pematangsiantar, (2) increase student learning outcomes in Microprocessor and Microcontroller learning by applying the Problem Based Learning model at SMK Negeri 2 Pematangsiantar. This research was conducted at SMK Negeri 2 Pematangsiantar for 1 month starting from August 2019. The subjects of this study were 22 students of class X1 TAV 1. The action in this study consisted of two cycles, namely Cycle I and Cycle II. Cycle I was carried out using the Problem Based Learning model. The results of the first cycle showed that 45.63% of students were active and the mean score of vocational competence students for Microprocessor and Microcontroller was still 56.82. However, these results do not meet the action indicators, namely 75% of students get a value > 75, then second cycle II is carried out. Cycle II carried out the same application. In cycle II 84.38% of students are active, and the average value of vocational competence for Microprocessors and Microcontrollers increases to 80.27. So it can be concluded that the learning process using the Problem Based Learning model can increase the activeness and ability of students in learning vocational competencies in Audio Video Engineering. The implication is that teachers must apply innovative and creative learning models. And it is suggested that Electronics Engineering teachers can improve their teaching skills to be more communicative and active in participating in various pieces of training.